O regime das tutelas de urgência à luz do princípio da efetividade do processo: possibilidades de mudança - Rattacaso, Marcus Claudius Saboia (2011)
Throughout this paper, we examine critically the procedures of the precautionary and anticipatory, whose analysis led us to propose reformulations in the text of the Code of Civil Procedure. At other times, not even deem it necessary to undertake formal changes in the legal text, because we infer that any innovations relevant to the study of emergency guardianship can be realized by means of interpretations carried out by academics and legal professionals, highlighting the role of judges. Certify that the techniques of urgency, as different procedural mechanisms to safeguard the most distinct property of life, should be studied under the optical principle of effectiveness of the process, which, in turn, finds support in principle of access to justice. This means that the emergency measures will also be guided by the idea of speed, fitness, seeking practical results and conforming to social expectations, with the noble task of combating the deleterious effects of the time the rights of persons and the functionality of the process. Despite the common features and the presence of the same matrix Constitution, the Code of Civil Procedure outlined different procedures for such measures, which implies the creation of formal obstacles to the achievement of effectiveness. Therefore, we propose to systematize the tutelage of urgency, and discussed the possibility of other changes, like the end of the autonomy of the process of appointments and interim precautionary typical, full fungibility between the techniques, relaxing the criterion of irreversibility of the measure and anticipatory institution of the figure of the stabilization of guardianship.